Influência da exposição ao modafinil sobre a preferência por anfetamina em diferentes períodos do desenvolvimento - Dias, Verônica Tironi (2019)
Addiction, which is characterized by the desire and the search for the drug, despite negative consequences, is a serious health problem, causing impairments to the individual, your family, and society. Thus, the developing of strategies to better understand neurobiological mechanisms related to this disorder are extremely relevant. Studies revealed that adverse experiences during the adolescence period could lead to neural circuit impairments facilitating neuropsychiatric disorders development, which could be manifested throughout life and even into adulthood. In this perspective, the inadequate use of licit prescribed psychostimulant drugs during adolescence has become a social concern nowadays. The objective of the current study was to evaluate the influence of modafinil (MOD) administration, a prescription drug, during adolescence on the conditioned place preference (CPP) for amphetamine (AMPH) in rats. The study is based on the hypothesis that prolonged MOD exposure during adolescence could modify the expression of molecular biomarkers related to memory (pro-BDNF, BDNF, Trk-B e GDNF) and targets of the mesolimbic dopaminergic pathway (D1R, D2R, DAT, TH e VMAT-2), affecting the cerebral oxidative status leading to behavioral alterations. From the pilot study (experimental protocol I), when we evaluate the MOD (64mg/kg p.o.) exposure influence on adolescent rats for 14 days, MOD improves short-term memory without causes changes in locomotor or anxiety parameters in the animals. Concerning the oxidative status, the MOD increased the catalase (CAT) activity decreasing oxidative damage markers in the prefrontal cortex, striatum and ventral tegmental área (VTA), as one exception the hippocampus, which MOD did not exert significative influence on the parameters evaluated. From the experimental protocol II, adolescent animals were exposed to MOD and consecutively conditioned with AMPH in the CPP paradigm in adulthood, when we observed that MOD reduced the preference for the drug, preventing locomotor alterations, anxiety-like symptoms, and memory impairments during withdrawal. MOD also showed antioxidant activity and beneficial influences on biomarkers related to memory (pro-BDNF, BDNF, and Trk-B), acting as a modulator of the hippocampal dopaminergic system (DAT, D1R, and D2R). The experimental protocol III was aimed to evaluate whether the same MOD beneficial influences would be repeated when these animals were AMPH-exposed still during adolescence. Again, MOD exposure reduced AMPH-CPP reducing the anxiety-like symptoms during withdrawal. Oxidative and molecular alterations in the dopaminergic system were observed in the VTA and striatum of this animals when MOD exerted an upregulation of striatal dopaminergic targets (TH, DAT, D1R, and D2R) after AMPH exposure, possibly preventing the decrease of dopamine levels during withdrawal and this could be reflected in the behaviors presented. From the experimental protocol IV, the MOD exposure occurred after AMPH-CPP was established, it was proposed as a treatment in the relapse. Such approach showed that MOD treatment prevented the AMPH relapse acting beneficially on memory. At the molecular level, the MOD caused beneficial changes in the dopaminergic system as well in neurotrophins related to the maintenance of this pathway upon AMPH exposure in the ventral striatum. In conclusion of these studies, it is possible to infer that MOD exerted beneficial behavioral effects on the preference and relapse for AMPH when administered during adolescence. Those behaviors occurred together with positive responses on oxidative status and molecular in brain areas related to addiction. So far, until this moment it is possible to propose that MOD could be acting as a modulator of the dopaminergic system against the damage caused by AMPH in rats.